Implementasi Strategi Pemasaran Melalui Social Media Marketing Pada UMKM Sugarbelly_id - Edy Yulianto Putra; Tasya Gebee Hasvia; Natasya Sapitri; Nisa Ardhany Damanik; Yeffy Yeffy (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This research discusses how to optimize marketing through social media at Sugarbelly_id SMEs. Currently Sugarbelly_id is facing fierce competition from other MSMEs selling similar products. This obstacle was factored in by the owner's lack of understanding of the latest business strategy developments which caused sugarbelly_id to have little engagement from target consumers and a brand image that had not yet been formed. So this study aims to provide an understanding regarding good Social Media Marketing strategies for sugarbelly_id SMEs and help optimize the use of social media and online platforms to build a more effective and attractive Brand Image and increase promotion using digital tools that guarantee increased engagement. The method used is descriptive qualitative analysis which is collected through interviews with the owner, surveys through questionnaires and observations which then analyze the appropriate strategy. The results obtained are that Sugarbelly_id SMEs already have a good brand image and the number of followers on the Sugarbelly_id Instagram account has increased from before, which was 350 followers. In addition, the number of Profile Visits on the Sugarbelly Instagram account has also increased, reaching 1,801 visitors in the last 6 days.